1996
DOI: 10.1016/0375-9474(96)00156-x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Hartree-Fock+BCS calculation with Skyrme SIII force

Abstract: We have performed deformed Hartree-Fock+BCS calculations with the Skyrme SIII force for the ground states of even-even nuclei with 2 ≤ Z ≤ 114 and N ranging from outside the proton drip line to beyond the experimental frontier in the neutron-rich side. We obtained spatially localized solutions for 1029 nuclei, together with the second minima for 758 nuclei. The single-particle wavefunctions are expressed in a three-dimensional Cartesian-mesh representation, which is suitable to describe nucleon skins, halos, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 48 publications
9
113
0
Order By: Relevance
“…These gross features are consistent with available experimental data [60][61][62][63][64][65][66] and previous theoretical calculations [19,21,22,49,[67][68][69][70][71][72][73][74][75][76][77].…”
Section: Quadrupole Deformationssupporting
confidence: 92%
See 2 more Smart Citations
“…These gross features are consistent with available experimental data [60][61][62][63][64][65][66] and previous theoretical calculations [19,21,22,49,[67][68][69][70][71][72][73][74][75][76][77].…”
Section: Quadrupole Deformationssupporting
confidence: 92%
“…In the present calculation, the radius of the spherical container and mesh spacing are set to R mesh = 10.0 fm and h = 1.0 fm, respectively. Tajima et al [49,50] have carefully examined possible errors due to the use of the mesh size h = 1.0 fm and they found that, since discretization errors are essentially independent of the nuclear shape, deformation energies obtained with this mesh size are quite accurate (see also [51]). Actually, we have constructed the new Skyrme-HFB code by extending the cranked Skyrme-HF code [52] written previously and applied to the investigation of the yrast structure of 32 S, so that the cranking term can be included.…”
Section: Two Basis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pairing energy is calculated for the constant monopole pairing interaction with a smooth truncation for the model space. We follow the prescription given by Tajima et al [17], which is equivalent to the following choice of G kl from Eq. (61),…”
Section: A Treatment Of the Pairing Energy Functionalmentioning
confidence: 99%
“…To determine the pairing strength constant g for each nuclei, we again follow the prescription of Ref. [17], which is practically identical to the one in Ref. [18].…”
Section: A Treatment Of the Pairing Energy Functionalmentioning
confidence: 99%